A comparative review one-stage and two-stage dental implants - Alfaer, Ali S.; Alharbi, Nouf Y.; Alsulami, Atheer A.; Alharthi, Saad M.; Modahi, Fawaz H.; Modahi, Nayif H.; Himdi, Ahmed T.; Almanidi, Noor Y.; Aljuaid, Majed K.; Yankasar, Rawan A.; Al Hutaylah, Hussain A. (International Journal Of Community Medicine And Public Health, 2023)
Dental implants have been used as an effective treatment for missing teeth. Dental implantology has a long history that reaches back to ancient times when attempts were made to replace missing teeth with various materials. Modern dental implants are designed to osseointegrate, where the implant fixture fuses with the jawbone. The surgical procedure involves placing the implant, followed by the adaptation of the surrounding tissue. There are two main surgical techniques: one-stage surgery and two-stage surgery. One-stage surgery involves placing the implant and allowing a healing abutment to protrude through the gums. This eliminates the need for a second surgery but carries the risk of overloading the implant during the healing phase. Two-stage surgery is the standard approach, where the implant is initially submerged, and a second surgery is performed to connect the abutment. The choice between one-stage and two-stage surgery depends on many factors, including bone quality, clinical parameters, and aesthetic considerations. One-stage surgery offers quick aesthetics but can pose a higher risk of implant failure due to early loading. Two-stage surgery provides a higher success rate but requires two surgical procedures.